Ethnobotany of fruit species native to paramos and cloud forests of Northern Peru - Torres-Guevara, Fidel Ángel; Ganoza-Yupanqui, Mayar Luis; Mantilla-Rodriguez, Elena; Suárez-Rebaza, Luz Angélica; Bussmann, Rainer W. (Ethnobotany Research and Applications, 2023)
Background: This study was carried out in the paramos and cloud forests of the Andes of the department of Piura of Northern Peru, and aimed to document the native fruit species known and culturally used by the communities around these ecosystems. Methods: The Use Value and Importance indices were applied. An intercultural communication approach was used to achieve the consensus of participation of community organizations in the registration of interviews and field collections based on the timing established by the communities to collect the species. Results: For a total of 49 fruit species ecological zone, phenology, nutritional and ethnomedicinal use were described. Of these 39 (80%) were not traditionally commercialized in the markets and only used by the communities in their nutrition and/or treatment of diseases. Overall, 27 species (55%) had nutritional and medicinal use; and among the 39 non-traditional species, 22 had dual use. Conclusions: The traditional knowledge of the communities around the paramos and cloud forests indicated the presence of 39 fruit species not known in the market, but with traditional consumption, which makes them promising native species for science, innovation, and ecologically sustainable profitable reforestation. Keywords: Ethnobotany, Andean fruit trees, paramos, cloud forests, reforestation, functional foods, nutraceuticals.